PENGARUH KEPEMILIKAN ASING TERHADAP NILAI PERUSAHAAN DENGAN PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY SEBAGAI VARIABEL INTERVENING - Aldila Khairina Sissandhy; Sudarno Sudarno (Diponegoro Journal of Accounting, 2014)
This study aimed to examine the effect of foreign ownership on firm value with Corporate Social Responsibility as an intervening variable. The use of CSR as an intervening variable because firms with foreign ownership has increased interest in CSR and CSR program is one factor that can increase the value of the firm value measured by Tobins'Q company.The study was conducted using purposive sampling method in manufacturing companies with criteria (1) manufacturing company listed on the Stock Exchange in 2009 to 2012 (2) Companies that issue and publish an annual report, especially social accountability reports from the period of 2009 up to 2012 complete. Based on 152 samples obtained criterion called the company for three years of observation. Then, there are 12 samples including outliers that must be excluded from the study sample. thus, the final number of viable samples observed is 140 companies. The analysis technique used is multiple regression analysis.The results of this study indicate that foreign ownership has a significant effect on firm value and foreign ownership also has a significant effect on CSR. CSR is not an intervening of foreign ownership on firm value.